2014
DOI: 10.14306/renhyd.18.3.67
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de dislipidemia y sus factores de riesgo en niños y adolescentes con sobrepeso y obesidad

Abstract: Esta obra está bajo una Licencia Creative Commons Atribución-NoComercial-SinDerivadas 3.0 Unported. Más información: http://creativecommons.org/licenses/by-nc-nd/3.0/deed.es_CO www.renhyd.org Introducción: Debido a que el sobrepeso y la obesidad frecuentemente se acompañan de complicaciones metabólicas, el objetivo del presente estudio es estimar la prevalencia de dislipidemia, sus factores de riesgo (FR) y el grado de concordancia entre los valores de corte de triglicéridos (TG) y HDL-C, según Cook y col. y l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
1
2
0
1
Order By: Relevance
“…The obtained results of hyperlipidemias (33.8%) match with investigations developed in South American countries between 2013 and 2017, the general prevalence of which are found related to hyperlipidemias in the young adult population, with maximum values of 87.7% and a minimum of 13.4%, media between (32.0% and 43.5%) [29,30,31,32,33,34,35,36], and with national studies, the prevalence was from 36.6% to 74.7% [1,10,15,37]. This shows that in the vast majority of low and medium-income countries, the young adult population is potentially vulnerable to the future development of multiple ENTs at an early age.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The obtained results of hyperlipidemias (33.8%) match with investigations developed in South American countries between 2013 and 2017, the general prevalence of which are found related to hyperlipidemias in the young adult population, with maximum values of 87.7% and a minimum of 13.4%, media between (32.0% and 43.5%) [29,30,31,32,33,34,35,36], and with national studies, the prevalence was from 36.6% to 74.7% [1,10,15,37]. This shows that in the vast majority of low and medium-income countries, the young adult population is potentially vulnerable to the future development of multiple ENTs at an early age.…”
Section: Discussionsupporting
confidence: 84%
“…Regarding specific hyperlipidemias, the prevalence of hypertriglyceridemia was 12.8%, with a higher manifestation in men than in women [29,30,35,38]. To a national level, some studies found prevalence rates of hypertriglyceridemia from 13.8% to 41.8% [1,37], suggesting that the increase in the level of plasmatic lipoproteins rich in TG (LPRTG) and atherogenic particles is the main risk metabolic factor for the development of atherogenic dyslipidemia, states of insulin-resistance, and atherosclerotic disease [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Las dislipidemias en niños y adolescentes constituyen un importante factor de riesgo para sufrir patologías cardiovasculares 1 . Estas enfermedades representan la primera causa de morbimortalidad en los países desarrollados 2,3 , hecho que cobra mayor relevancia teniendo en cuenta que sus factores precursores y determinantes pueden aparecer en la infancia 4,5 .…”
Section: Introductionunclassified